Pemasaran Digital Dengan Mengetahui Risiko dan Mitigasi Risiko Pada UMKM di Kecamatan Gunung Kaler - Yanti Susanti; Ela Nurlela; Desti Kurniati; Esti Damara (LKP KARYA PRIMA KURSUS, 2025)
This community service activity aims to enhance the ability of MSME actors in the Gunung Kaler District to utilize digital marketing effectively by understanding the various potential risks and the mitigation strategies that need to be implemented. In the digital era, MSMEs face challenges such as data security threats, errors in content management, low digital literacy, and reputation risks arising from online customer interactions. Through training sessions, direct mentoring, and case simulations, this program provides practical knowledge enabling MSMEs to identify risks, minimize negative impacts, and optimize digital marketing efforts to improve business competitiveness. The offered solutions include educational activities delivered through lectures, interactive discussions, and the measurement of participants’ understanding using pre-test and post-test instruments. The activity was conducted in the Gunung Kaler District, Tangerang Regency, involving 21 MSME participants. Initial implementation results indicated a lack of understanding among participants regarding the effective use of digital marketing through risk identification and mitigation, as reflected in the higher post-test scores and significant regression model findings. The R Square value of 0.158 and F value of 2,881. These results indicate that the Digital Marketing and Risk Mitigation variables simultaneously explain only 15.8% of the MSME Performance variance, nevertheless, the program successfully improved participants’ knowledge and awareness of the importance of digital risk 1qmanagement for strengthening business competitiveness and sustainability.